What Elements of the Inflammatory System Are Necessary for Epileptogenesis In Vitro?1,2 - Park, Kyung-Il (eNeuro, 2015)
Epileptogenesis in vivo can be altered by manipulation of molecules such as cytokines and complement that subserve intercellular signaling in both the inflammatory and central nervous systems. Because of the dual roles of these signaling molecules, it has been difficult to precisely define the role of systemic inflammation in epileptogenesis. Organotypic hippocampal brain slices can be maintained in culture independently of the systemic inflammatory system, and the rapid course of epileptogenesis in these cultures supports the idea that inflammation is not necessary for epilepsy. However, this preparation still retains key cellular inflammatory mediators. Here, we found that rodent hippocampal organotypic slice cultures depleted of T lymphocytes and microglia developed epileptic activity at essentially the same rate and to similar degrees of severity as matched control slice cultures. These data support the idea that although the inflammatory system, neurons, and glia share key intercellular signaling molecules, neither systemic nor CNS-specific cellular elements of the immune and inflammatory systems are necessary components of epileptogenesis.